Cointegration and spatial price transmission among wheat and wheat-flour markets in Afghanistan. Issue 30 (27th June 2017) - Hassanzoy, Najibullah; Ito, Shoichi; Isoda, Hiroshi; Amekawa, Yuichiro
ABSTRACT: This article examines cointegration and spatial price transmission among Afghan wheat and flour markets as well as their linkages with those of supplier countries and global markets. Unit root tests, consistent momentum threshold autoregressive (M-TAR) models and vector error correction models (asymmetric and symmetric) are employed to achieve research objectives. The results suggest that provincial wheat and flour markets may have a long-run relationship with principal market of Kabul. Afghan wheat and flour markets may also be cointegrated with their respective global, Kazakh and Pakistani markets. While provincial wheat markets might adjust to divergence from their long-run equilibrium with Kabul wheat market, some of the provincial flour markets may not respond to deviation from their long-run equilibrium with Kabul flour market. The speed of adjustment towards the long-run Afghan–Pakistani and Afghan–Kazakh equilibrium may be faster for Afghan flour than wheat markets. The equilibrium adjustment coefficients are generally small and market imperfections may exist, however. A shock in Kabul wheat and flour markets may have long-lasting effect on the respective provincial markets whereas a shock in global wheat and Pakistani, and Kazakh wheat and flour markets might have transitory effect on the corresponding Afghan markets.